2018
DOI: 10.1016/j.jspd.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

S2 Alar Iliac Fixation in Long Segment Constructs, a Two- to Five-Year Follow-up

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
1
18
2
Order By: Relevance
“…S2AI screw loosening was found in 67% of patients, and S1 screw loosening in 12% of patients 2 years after ASD surgery. Previous studies found that S2AI screw loosening was found in 2.9%-10.4% [5,7,11]. The incidence of S2AI screw loosening found in our study was more than that reported previously.…”
Section: A B C D Econtrasting
confidence: 53%
See 2 more Smart Citations
“…S2AI screw loosening was found in 67% of patients, and S1 screw loosening in 12% of patients 2 years after ASD surgery. Previous studies found that S2AI screw loosening was found in 2.9%-10.4% [5,7,11]. The incidence of S2AI screw loosening found in our study was more than that reported previously.…”
Section: A B C D Econtrasting
confidence: 53%
“…The incidence of S2AI screw loosening found in our study was more than that reported previously. The difference was because we evaluated screw loosening using CT, while previous studies used conventional radiographs [7,11]. We consider that our 2-year postoperative evaluation using CT is more accurate than that of previous studies.…”
Section: A B C D Ementioning
confidence: 96%
See 1 more Smart Citation
“…Smith et al found that 86 patients without pre-operative pseudoarthrosis who underwent S2AI screw fixation had a 95.3% fusion rate at 2 to 5 years of follow-up [22]. Interestingly, 10.4% of patients had evidence of S2 loosening on imaging, including two cases that required hardware removal and one that required S2AI instrumentation exchange after pseudarthrosis developed.…”
Section: Discussionmentioning
confidence: 99%
“…By using a more medial starting point than with traditional iliac screws, the need for offset connectors was eliminated, which improved the profile of the implant construction, limiting soft tissue dissection, and avoiding the typical skin complications of the iliac screws. [7][8][9][10] The original description of the technique was made in an American pediatric and adult population. 9,10 There is also a description in Asian populations.…”
Section: Introductionmentioning
confidence: 99%